2017
DOI: 10.1007/s00232-017-9972-z
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Newly Platinum(II) with Tris(2-carboxyethyl)phosphine Complex with DNA and Model Lipid Membrane

Abstract: Structural properties of plasmid DNA and model lipid membrane treated with newly synthesized platinum(II) complex cis-[PtCl2{P(CH2CH2COOH)3}2] (cis-DTCEP for short) were studied and compared with effects of anticancer drug cisplatin, cis-[Pt(NH3)2Cl2] (cis-DDP for short). Time Correlated Single Photon Counting Fluorescence Correlation Spectroscopy (TCSPC-FCS) was employed to study interactions between those platinum complexes and DNA. The TCSPC-FCS results suggest that bonding of cis-DTCEP derivative to DNA le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Complex 1 reactivity with a dsDNA has been recently studied in the presence of a model lipid membrane [ 31 ]. The results suggested that bonding of complex 1 to DNA leads to a much more compact structure than cisplatin's DNA bonding, revealing complex 1 interacts by hydrogen bonding on the hydrophilic regions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Complex 1 reactivity with a dsDNA has been recently studied in the presence of a model lipid membrane [ 31 ]. The results suggested that bonding of complex 1 to DNA leads to a much more compact structure than cisplatin's DNA bonding, revealing complex 1 interacts by hydrogen bonding on the hydrophilic regions.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of oxygen is a very important condition for the isolation of the pure compound; otherwise, the TCEP oxidizes. Monitoring the reaction by 31 P-NMR detects a new signal at 15.9 ppm highly shifted from the free ligand signal at 56.7 ppm.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, a decrease in the wavenumber of the maximum of this band indicates that the lipid phosphate polar head group is located in more polar environments and that head group hydration increased [62]. Similar changes are also observed when the membrane embeds compounds having OH groups in their structure, which may also form hydrogen bonds with the phosphoric group lipids, e.g., polyphenols, plant extracts, carotenoids, complexes of platinum [61,[63][64][65][66][67]. Therefore, the band located at 1235 cm −1 (for RBCMs) shifted toward lower frequencies in the presence of lactones probably indicates an interaction via hydrogen bonds between the PO 2 -group of the lipid and lactone 1 molecules.…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 77%
“…Also, studies on the interaction of Pt‐TCEP with plasmid DNA revealed that it has a stronger folding effect than cisplatin. Additionally, it was shown that it interacts with hydrophilic region of the lipid bilayer and slightly increases the phospholipid's main phase transition temperature causing decrease of its fluidity . In our previous study, we showed that the compound had cytotoxic and pro‐apoptotic activity against canine leukaemia and lymphoma cell lines.…”
Section: Introductionmentioning
confidence: 92%